Proposed new interior design scheme of Kopiesatu Café at No 67, Jalan Diplomatik2, Presint 15, 62030, Putrajaya / Athirah Omairi - Omairi, Athirah (Faculty of Architecture, Planning and Surveying, 2010)
One of the factors that made a business successful is the design of the interior. Design means solving problems. Interior design means solving problem in the interior. As for a cafe, there are many aspects that we should consider before producing a final proposal. The very important aspect that we should think deeply about when we talk about cafe and restaurant is the circulation and the traffic flow. It is very important to determine the space requirement in order to make or produce a good layout plan. The space requirement is based on client needs. Every space in the interior should be based on client’s requirement. Interior designer could not simply propose a design without analyzing the requirement from the client. The client requirement can be divided into space requirement, general requirement and system requirement. The interior design of the cafe should also relate to the environment of the site. Therefore, it is very crucial to make a good research and analyze the proposed site. The final design proposal is the final stage of all design process. It is where the final proposal is presented for client’s approval. In this project, proposed new interior design for KopiesSatu Cafe, the design process are the same as the above. The client of this project whom is KopieSatu, is a company organized by FAMA. The aim of this project is to provide KopieSatu with a standard and suitable identity through its interior design in order for them to franchise their product globally.